Sentinel surveillance of Lymphatic filariasis, Schistosomiasis, Soil transmitted helminths and Malaria in rural southern Malawi - Msyamboza, Kelias (The Medical Association Of Malawi, 2010)
BACKGROUND: Baseline prevalence and knowledge, attitude and perception (KAP) survey is a prerequisite for mass drug administration for the control of Lymphatic filariasis (LF) and other neglected tropical diseases. METHODS: In preparation for the first mass drug administration for LF elimination, a baseline survey was conducted in six sentinel sites in the southern Malawi, amongst participants aged five years or more. A standard questionnaire was used to obtain data on socio-demographic factors, ownership and use of bed nets, previous ingestion of ivermectin and KAP toward hydrocele and lymphoedema. Finger prick blood samples were collected from 22:00 to 01:00 hours for LF microscopy, malaria and haemoglobin examination. Stool and urine samples were collected for internal helminths and schistosomiasis respectively. RESULTS: A total of 1, 903 participants were enrolled. Knowledge on the cause of hydrocele and lymphoedema was low in all the sentinel sites (16%–42%, 10%–24% (respectively). Sexual intercourse with a menstruating woman, bad weather and HIV/AIDS were perceived causes of hydrocele. Microfilaraemia prevalence was 1.5% and varied little between sentinel sites (1.0%–2.1%). Childhood urinary schistosomiasis was common in Phalombe (94.9%) and Blantyre (26.9%). CONCLUSION: Integrated approach and understanding of the community KAP is vital or successful implementation of LF elimination programme.